Sistem Pendukung Keputusan untuk Penilaian Staff Divisi Purchasing Menggunakan Metode SAW dan ROC - Hidayatullah, Syarif; Santoso, Heri Bambang (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
Purchasing Division Staff is an individual who is responsible for managing the procurement process of goods or services needed by the organization. They have a crucial role in ensuring the availability of materials or services of the highest quality, competitive prices, and delivery times that suit operational needs. Their main duties include analyzing needs, finding and evaluating suppliers, negotiating contracts, and monitoring supplier compliance with agreed agreements. The combination of the SAW and ROC methods creates an effective approach in multi-criteria decision support systems, by integrating the strengths of both methods. The advantage of this combination is the integration of ROC which ensures the weighting of criteria is based on the order of importance systematically, while SAW simplifies the process of calculating the final score. The ranking results obtained by TF Staff ranked the highest with a score of 0.8736, showing the most superior performance among all purchasing staff. The second position was occupied by AE Staff with a score of 0.8568, who also had a very good performance although slightly lower than TF Staff. DP staff is in third place with a score of 0.8086, still in the strong and competitive performance category. These results provide an objective picture of the order of purchasing staff performance based on the criteria that have been evaluated.